A Comparison Study of the Effect on IBS-D Rats among Ginger-Partitioned Moxibustion, Mild Moxibustion, and Laser Moxibustion - Chao Sun (Hindawi Limited, 2021)
Background. Diarrhea-predominant irritable bowel syndrome (IBS-D) is a functional gastrointestinal disorder that severely affects patients’ life. Moxibustion is believed to be an effective way to treat IBS-D. However, the therapeutic effects and the underlying mechanisms in symptom management of IBS-D by different moxibustion therapies remain unclear. Methods. IBS-D model rats were divided into groups and treated with ginger-partitioned moxibustion (GPM), mild moxibustion (MM), and laser moxibustion (LM) at a temperature of 43°C, respectively. The temperature curves of acupoints were recorded during interventions. The therapeutic effects were evaluated on the basis of general condition, stool, and hematoxylin-eosin staining of the colon tissue. Moreover, the expression of transient receptor potential vanilloid 1 (TRPV1) receptors in both acupoint tissue and colon tissue was analyzed by immunohistochemistry. Results. After moxibustion treatment, the symptoms were improved. The expression of TRPV1 was increased in acupoint tissue and decreased in colon tissue. GPM and MM showed a more significant influence on IBS-D rats compared with LM. The temperature profile of GPM and MM was wave-like, while LM had an almost stable temperature curve. Conclusion. GPM, MM, and LM could improve the symptoms in IBS-D rats. Moxibustion might activate TRPV1 channels in the acupoint tissue and induce acupoint functions, which in turn inhibit the pathological activation state of the colon’s TRPV1, followed by improvements in abdominal pain and diarrheal symptoms. LM with stable temperature might lead to the desensitization of TRPV1 receptors and the tolerance of acupoint. GPM and MM provided dynamic and repetitive thermal stimulations that perhaps induced acupoint sensitization to increase efficacy. Therefore, dynamic and repetitive thermal stimulation is recommended in the application of moxibustion.